Exploring Technology Integration and Pedagogical Practices in Public and Private Secondary Schools - Dr. Zahid Ullah; Shakira Munir; *Dr. Sumera Imran (Social Science Review Archives, 2025)
The integration of technology in secondary school classrooms has emerged as a critical factor in enhancing teaching effectiveness and student learning outcomes. This study explores the perceptions and experiences of teachers and students regarding technology integration and pedagogical practices in public and private secondary schools of District Mardan, Khyber Pakhtunkhwa, Pakistan. Using a qualitative research design, semi-structured interviews were conducted with ten teachers (five public, five private) and ten students (five public, five private) to examine how digital tools are utilized, the instructional strategies employed, and the contextual factors influencing effective integration. Findings reveal that private schools demonstrate higher access to technological resources and more frequent use of interactive pedagogical strategies, such as project-based learning, group work, and student-centered activities, whereas public schools face challenges related to limited infrastructure, inadequate teacher training, and inconsistent administrative support. Despite these differences, both school types acknowledge the potential of technology to enhance student engagement, motivation, and comprehension. The study highlights that pedagogical practices mediate the effectiveness of technology integration, with teachers’ instructional skills, confidence, and professional development playing pivotal roles in shaping student outcomes. The research underscores the importance of school support systems, targeted professional development, and context-specific strategies to maximize the benefits of technology in classrooms. By comparing public and private schools, this study provides valuable insights into disparities in resource availability, teaching practices, and student experiences, offering evidence-based recommendations for policy and practice. The findings contribute to the broader discourse on digital education in developing country contexts and emphasize the need for strategic interventions to foster equitable and effective technology-enhanced learning environments.